Impact of concomitant COVID-19 on the outcome of patients with acute myocardial infarction undergoing coronary artery angiography - Terlecki, Michał; Wojciechowska, Wiktoria; Klocek, Marek; Olszanecka, Agnieszka; Bednarski, Adam; Drożdż, Tomasz; Pavlinec, Christopher; Lis, Paweł; Zając, Maciej; Rusinek, Jakub; Siudak, Zbigniew; Bartuś, Stanisław; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The impact of COVID-19 on the outcome of patients with MI has not been studied widely. We aimed to evaluate the relationship between concomitant COVID-19 and the clinical course of patients admitted due to acute myocardial infarction (MI). Methods: Comparison of retrospective data between patients with MI who were qualified for coronary angiography with concomitant COVID-19 and control group of patients treated for MI in the preceding year prior to the onset of the pandemic. In-hospital clinical data and the incidence of death from any cause on 30 days were obtained. Results: Data of 39 MI patients with concomitant COVID-19 (COVID-19 MI) and 196 MI patients without COVID-19 (non-COVID-19 MI) were assessed. Compared with non-COVID-19 MI, COVID-19 MI were in a more severe clinical state on admission (lower systolic blood pressure: 128.51±19.76 vs 141.11±32.47 mmHg, p=0.024, higher: respiratory rate (median [interquartile range], 16 (14-18) vs 12 (12-14) /min, p<0.001), GRACE score (178.50±46.46 vs 161.23±49.74, p=0.041), percentage of prolonged (>24 hours) time since MI symptoms onset to coronary intervention (35.9% vs 15.3%; p=0.004) and cardiovascular drugs were prescribed less frequently (beta-blockers: 64.1% vs 92.8%, p=0.009, angiotensin-converting-enzyme inhibitors/angiotensin receptor blockers: 61.5% vs 81.1%, p<0.001, statins: 71.8% vs 94.4%, p<0.001). Concomitant COVID-19 was associated with 7-fold increased risk of 30-day mortality (HR 7.117; 95% CI: 2.79- 18.14; p<0.001). Conclusions: Patients admitted due to MI with COVID-19 have an increased 30-day mortality. Efforts should be focused on the infection prevention and implementation of optimal management in order to improve outcomes in those patients